Analysis of the Impact of Clinical Factors on Low-Intensity Extracorporeal Shockwave Therapy for Erectile Dysfunction - Oginski, Natalie; Apel, Hendrik; Richterstetter, Mario; Lieb, Verena; Fiebig, Christian; Goebell, Peter; Wullich, Bernd; Sikic, Danijel (Urologia Internationalis, 2022)
Introduction: Predictive factors for the treatment success of low-intensity extracorporeal shockwave therapy (Li-ESWT) for erectile dysfunction (ED) are still under debate. Methods: Li-ESWT was performed in 50 patients suffering from ED by applying 3,000 shock waves once a week over a period of 6 weeks. Treatment success was defined as an increase in the International Index of Erectile Function 5 (IIEF-5) score by >= 5 points or an Erectile Hardness Score (EHS) of >= 3 points. IIEF-5 and EHS were measured at baseline and at 3 and 6 months of follow-up. Results: Treatment success according to either the IIEF-5 score or EHS at any time of follow-up was achieved in 28 patients (56%). Twenty-five patients (50%) experienced an improvement during the first 3 months, which lasted for 6 months in 8 cases (16%). Three patients reported improved erectile function only after 6 months. When stratifying the cohort with regard to potential influencing factors, a significantly improved IIEF-5 score could be achieved in men with cardiovascular risk factors (p = 0.026) and in men with antihypertensive medication (p = 0.009). Men without cardiovascular risk factors showed no therapeutic benefit from Li-ESWT. Discussion/Conclusion: Li-ESWT is a valid but often short-lived treatment option for ED, especially in men with cardiovascular risk factors or controlled hypertension. Future studies should assess the feasibility and safety of repeated applications of Li-ESWT.
CRIS-Team WoS Importer:2022-03-04